Hypertensive emergency as a complication of brachial plexus block. (8th March 2011) - Chakithandy, Sajith; Kelly, Paul; Barron, James
Abstract : The authors report a case of hypertensive emergency (defined as systolic blood pressure >180 mm Hg and diastolic blood pressure >110 mm Hg with end organ damage) following brachial plexus blockade in a hypertensive lady with unstable angina. The authors describe blocking of baroreceptor reflexes by the local anaesthetic as a putative mechanism and suggest that this potentially serious complication should be considered when planning this particular anaesthetic technique.